VD_FINDINFO Décision / 2021 / 993 vom 27. September 2021 - VD Tribunal cantonal (2021)
MOTIVATION DE LA DEMANDE, MESURE DISCIPLINAIRE | 38 LEP, 95 al. 1 LTF, 97 al. 1 LTF, 385 al. 1 CPP (CH), 393 CPP (CH)